The Influence of Quercus robur L. and Juglans rupestris Engelm. Plantations on the Properties of Steppe Soils - Olga E. Klimenko; Nikolay I. Klimenko (Лесной журнал, 2024)
The aim of the study has been to determine the condition of Quercus robur L. and Juglans rupestris Engelm. and their influence on the properties of segregated chernozems. The study was conducted in 2020–2021 in the steppe Crimea. The control has been a perennial grass fallow. To characterize the general condition of the trees, a 4-point scale for assessing the condition of the introduced species has been used. Standard methods have been used for soil analysis. A better preservation and a greater number of 50-year old plants in excellent and good condition have been established for Q. robur (67 и 56 %, respectively) compared to J. rupestris (48 и 42 %, respectively) in these environmental conditions, which is explained by the greater adaptive capabilities of oak as an indegenous species. Both tree crops have influenced soil properties. In their phytocenoses, a litter has been formed, more significant under J. rupestris. The dark humus horizon has also turned out to be thicker under the J. rupestris plantation (80 cm) than under the Q. robur plantation and the fallow (72 and 70 cm, respectively). Under Q. robur the soil density has been lower than under J. rupestris by 0.02–0.18 g/cm3. Under the woody plants, the soil structure has improved: the number of lumpy aggregates has decreased, and the number of agronomically valuable and granular particles has increased. The maximum coefficient of structure has been in the soil under the oaks (4.4–6.6), which exceeded the control by 2.5–4.9 times. Under the woody plants, carbonates have been significantly washed out of the soil profile, especially under J. rupestris. The pHH2O value of the alkaline soil under the woody plants has decreased by 0.2–0.4 and has been closely related to carbonate content (r = 0.83–0.91). The humus content under both species has been significantly higher than under the fallow – by 0.30–0.86 %. Afforestation has resulted in the accumulation of total forms of nutrients, to a greater extent under J. rupestris, and the C:N ratio has decreased. Tree species have stored more labile forms of nutrients in the soil. Soil desalination has been noted in the tree cenoses. Thus, J. rupestris and Q. robur are ecologically stable in the conditions of the central steppe of Crimea and can be used to increase forest cover in steppe areas. This will help improve soil fertility.